2018
DOI: 10.1029/2018jb015962
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic Observations of Weak Determinism in Rupture Evolution of Large Earthquakes

Abstract: The moment evolution of large earthquakes is a subject of fundamental interest to both basic and applied seismology. Specifically, an open problem is when in the rupture process a large earthquake exhibits features dissimilar from those of a lesser magnitude event. The answer to this question is of importance for rapid, reliable estimation of earthquake magnitude, a major priority of earthquake and tsunami early warning systems. Much effort has been made to test whether earthquakes are deterministic, meaning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…We have shown that the statistical properties of the subevent moment relative to the main event moment may be utilized for early magnitude estimates. Our results do not imply that earthquakes are deterministic in the sense that early nucleation is indicative of the entire evolution of rupture (Beroza & Ellsworth, 1996;Goldberg et al, 2018;Iio, 1995;Meier et al, 2017;Melgar & Hayes, 2017), but rather that we can exploit the patterns in earthquake complexity to statistically infer the future number and size of subevents from the first subevent. Our results are mostly practical for strike-slip events that tend to have shorter duration subevents.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…We have shown that the statistical properties of the subevent moment relative to the main event moment may be utilized for early magnitude estimates. Our results do not imply that earthquakes are deterministic in the sense that early nucleation is indicative of the entire evolution of rupture (Beroza & Ellsworth, 1996;Goldberg et al, 2018;Iio, 1995;Meier et al, 2017;Melgar & Hayes, 2017), but rather that we can exploit the patterns in earthquake complexity to statistically infer the future number and size of subevents from the first subevent. Our results are mostly practical for strike-slip events that tend to have shorter duration subevents.…”
mentioning
confidence: 64%
“…Furthermore, there is not yet an implementation of real-time source time function inversion, which would require an a priori knowledge of the source location and P wave Green's function (the latter can be precomputed and efficiently searched in databases). Goldberg et al (2018) and Minson et al (2018) indicate that, at best, magnitude estimates are slightly lower but track the evolution of cumulative moment release (green curve in Figure 4b). The advantage of using the scaling provided described in this paper is therefore a speed up, in the Palu example, of the duration of observation required to produce a final magnitude estimate by about 10 s from current methods.…”
Section: Possible Application To Earthquake Early Warningmentioning
confidence: 96%
See 1 more Smart Citation
“…More recently, Leyton et al () analyzed seismic and geodetic waveforms from earthquakes in the Chilean subduction zone, finding that EEW source characterization can be significantly improved using extended measurement time windows, which is inconsistent with the notion of rupture determinism. While these studies suggest that a purely deterministic rupture mechanism can likely be ruled out, a weak or probabilistic form of determinism may still be observed in some instances through careful analysis of seismic or geodetic data (Goldberg et al, ; Melgar & Hayes, ; Olson & Allen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consider the STFs of the events that have similar magnitudes to the Mentawai earthquake (Figure e). The protracted duration of the tsunami earthquake and slow growth to final PGD (Figure a; Goldberg et al, ), produced by the slow rupture of low rigidity rocks, leads to a low‐stress drop rupture (Ye et al, ; Yue et al, ) with a source spectrum (Figure f) that has a much lower corner frequency for tsunami earthquakes. It also leads to a larger coseismic slip for the given earthquake magnitude, as slip is inversely proportional to rigidity with respect to seismic moment.…”
Section: Resultsmentioning
confidence: 99%